LW-213 induces cell apoptosis in human cutaneous T-cell lymphomas by activating PERK–eIF2α–ATF4–CHOP axis - Yu, Xiao-xuan (Acta Pharmacol Sin, 2020)
Cutaneous T-cell lymphoma (CTCL) is characterized by a heterogeneous group of extranodal non-Hodgkin lymphomas, in which monoclonal T lymphocytes infiltrate the skin. LW-213, a derivative of wogonin, was found to induce cell apoptosis in chronic myeloid leukemia (CML). In this study, we investigated the effects of LW-213 on CTCL cells and the underlying mechanisms. We showed that LW-213 (1–25 μM) dose-dependently inhibited human CTCL cell lines (Hut-102, Hut-78, MyLa, and HH) with IC(50) values of around 10 μM, meanwhile it potently inhibited primary leukemia cells derived from peripheral blood of T-cell lymphoma patients. We revealed that LW-213-induced apoptosis was accompanied by ROS formation and the release of calcium from endoplasmic reticulum (ER) through IP(3)R-1channel. LW-213 selectively activated CHOP and induced apoptosis in Hut-102 cells via activating PERK–eIF2α–ATF4 pathway. Interestingly, the degree of apoptosis and expression of ER stress-related proteins were alleviated in the presence of either N-acetyl cysteine (NAC), an ROS scavenger, or 2-aminoethyl diphenylborinate (2-APB), an IP(3)R-1 inhibitor, implicating ROS/calcium-dependent ER stress in LW-213-induced apoptosis. In NOD/SCID mice bearing Hut-102 cell line xenografts, administration of LW-213 (10 mg/kg, ip, every other day for 4 weeks) markedly inhibited the growth of Hut-102 derived xenografts and prolonged survival. In conclusion, our study provides a new insight into the mechanism of LW-213-induced apoptosis, suggesting the potential of LW-213 as a promising agent against CTCL.